Comparative Assessment between Oral Health Education and Oil Pulling with Oral Health Education in Maintaining Periodontal Health: A Double Blinded Randomised Clinical Trial - Pathak, Ayushi; Chaturvedi, Pulkit; Dungarwal, Nitin; Joshi, Reenu; Sonowal, Poly Pratah; Pasari, Rohit (Journal of Neonatal Surgery, 2025)
Background: Oil pulling is an ancient Ayurvedic practice that involves swishing oil in the mouth to improve oral health. Traditionally, sesame oil and coconut oil have been the most commonly used oils due to their antimicrobial and anti-inflammatory properties. This practice is believed to reduce plaque accumulation, gingival inflammation, and improve overall oral hygiene by eliminating toxins and harmful bacteria from the oral cavity. Aim: This study aims to evaluate the effectiveness of oil pulling as an adjunct to oral health education in maintaining periodontal health compared to oral health education alone. Methodology: A double-blinded, randomized clinical trial was conducted over a 45-day period at the Department of Public Health Dentistry, Darshan Dental College and Hospital, Udaipur. Forty participants were randomly assigned to two groups: the control group (oral health education only) and the test group (oral health education with oil pulling). Participants in the test group performed oil pulling with coconut or sesame oil daily for 8–10 minutes. Gingival Index (Löe and Silness, 1963), Plaque Index (Silness and Löe, 1964), and Oral Hygiene Index-Simplified (OHI-S, Greene and Vermillion, 1964) were assessed at baseline (T0), 15 days (T1), and 30 days (T2). Data were analysed using SPSS software, with ANOVA and post-hoc tests determining statistical significance (p < 0.05). Results: The oil pulling group showed a significant reduction in plaque levels (p = 0.001), gingival inflammation (p = 0.002), and improved oral hygiene scores (p = 0.000) compared to the control group. The most significant improvements occurred between baseline and 15 days, with a continued but slower improvement from 15 to 30 days. The control group, which received only oral health education, showed no significant changes in any indices over the study period (p > 0.05). Conclusion: Oil pulling significantly enhances oral hygiene and reduces gingival inflammation and plaque levels when combined with oral health education. These findings suggest that oil pulling can be an effective, natural, and cost-effective adjunctive oral hygiene practice. Further long-term studies are recommended to establish standardized protocols and assess its broader clinical benefits.